Metode Pembelajaran Kitab Kuning Di Dayah Ma‘Had Al-‘Ulūm Dīniyyah Al-Islāmiyyah Mesjid Raya Mudi Mesra Samalanga, Aceh, Indonesia - M. Kausar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This study aimed to explore the learning of the kitab kuning (literally meaning yellow book) (traditional Islamic textbooks) at Dayah (traditional Islamic boarding school) Mudi Mesra Samalanga by using an analytical study in a methodological perspective. The study used the qualitative approach. Data were collected by observation, interview, documentation study, and Forum Group Discussion (FGD). The data analysis involved three stages: data reduction, data display, and conclusion drawing and verification. The data validity test used data credibility techniques in the form of extended observations, increased persistence in triangulation research, negative case analysis, and member check. The results of the study showed that in principle, the kitab kuning learning applied the halaqah method, in which the teacher sits opposite the students sitting around the teacher. From this learning system, the teacher has developed various learning methods. The methods that are most identical and authentic in learning kitab kuning at dayah include the Boh Bareh (Giving diacritical marks) method, the Surah Method, the Mubahastah and Mudhakarah method, the Niqasy method, the Muthala’ah method, and the Nazam Bait method. Apart from that, methods that are metaphysical are also taught to students to gain barakah (good) knowledge, by maintaining adab (attitude) towards teachers and maintaining adab towards kitab kuning as a source of learning that is sacred in nature. Further, the supporting factors in learning kitab kuning at dayah include the obligation to have kitab kuning, adequate facilities and infrastructure, dormitory system, as well as teacher loyalty and student discipline. On the other hand, the inhibiting factors consist of closer class positions, different physical endurance of the students, the saturation of the students, and the students’ lack of discipline during holidays.